2016
DOI: 10.1016/j.ijsu.2016.02.030
|View full text |Cite
|
Sign up to set email alerts
|

HAL-RAR (Doppler guided haemorrhoid artery ligation with recto-anal repair) is a safe and effective procedure for haemorrhoids. Results of a prospective study after two-years follow-up

Abstract: HAL-RAR is safe and almost painless technique and it has very good results in the control of haemorrhoidal symptoms. This procedure should be considered as an effective first treatment option for haemorrhoids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 20 publications
0
22
0
10
Order By: Relevance
“…Over the past two decades, knowledge of the anatomy of hemorrhoids has improved, leading to the introduction of new surgical technologies. This was accompanied by many studies comparing several surgical treatments including the Doppler-guided hemorrhoidal artery ligation (DG-HAL) with or without recto-anal repair (RAR) [ 9 11 ], a sutured hemorrhoidopexy [ 12 , 13 ], the stapled hemorrhoidopexy (SH) [ 14 – 16 ], and the traditional hemorrhoidectomy [ 17 – 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, knowledge of the anatomy of hemorrhoids has improved, leading to the introduction of new surgical technologies. This was accompanied by many studies comparing several surgical treatments including the Doppler-guided hemorrhoidal artery ligation (DG-HAL) with or without recto-anal repair (RAR) [ 9 11 ], a sutured hemorrhoidopexy [ 12 , 13 ], the stapled hemorrhoidopexy (SH) [ 14 – 16 ], and the traditional hemorrhoidectomy [ 17 – 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ratto et al [12] showed an absence of important complications, which are represented mainly by anal tenesmus (13% of cases). Hoyuela et al [13] reported a 2-year prospective study and concluded that THD is a safe and almost painless technique that offers very good results in the control of hemorrhoidal symptoms. Infantino et al [14] reported similar results to this multicentric prospective trial.…”
Section: Discussionmentioning
confidence: 99%
“…3 HAL results have been improved when associated with fixation of prolapsed tissue with mucopexy or recto-anal repair (RAR). [4][5][6][7][8][9][10][11][12][13][14][15] As previously stated, the primary aim of this study is to compare the postoperative pain of HAL-RAR with EH, and the secondary outcomes are the following: symptom resolution rates, postoperative morbidity, early recurrence, and changes in quality of life.…”
Section: Introductionmentioning
confidence: 99%